Accounting for π–π stacking interactions in the mesoscopic models of conjugated polymers. Issue 6 (24th June 2020) - Rudyak, Vladimir Yu.; Gavrilov, Alexey A.; Guseva, Daria V.; Tung, Shih-Huang; Komarov, Pavel V.
Abstract : Accounting for π–π interactions between conjugated polymer molecules via dynamic bonds allows their self-assembly into a lamellar morphology with π–π stacks. Abstract : Conjugated polymer films play a decisive role in the construction of photoactive elements in organic electronic devices. Their morphology is mainly determined by self-assembly processes during crystallization initiated by π–π interactions between aromatic rings. However, currently there are only very limited methods to construct polymer matrix models taking into account their crystallization in the framework of computer simulations. In this paper, we propose an extension of a mesoscale modeling methodology based on the dissipative particle dynamics method. We use poly(3-hexylthiophene) (P3HT) as a prototype of the mesoscopic model of polymer chains. To take into account the π–π interactions, we implement the formation and breaking of additional dynamic non-covalent bonds between coarse particles mapped to thiophene rings. We show that the introduction of dynamic bonds makes it possible to simulate the self-assembly of the conjugated polymer chains into a hexagonally packed cylinder morphology and lamellar morphology with large thiophene stacks.